Prosthodontic rehabilitation with overdenture based on gerostomatological principles - Klaudia Varga; János Vág (Hungarian Dental Association, 2024)
Introduction: Gerostomatology is a medical discipline dealing with the dental care of elderly patients. With advancing age, changes in tooth structure and tooth loss have a major impact not only on the oral health but also on general health. The loss of teeth in patients' life leads to reduced chewing and swallowing ability which affects the digestive system. In addition, a less aesthetic appearance and difficulties in speech affect the psychological state of the individual and impair the quality of social life. Case report: 70-year-old female patient with gerostomatological factors affecting dental treatment. She was dissatisfied with her previous dental prosthesis made according to the dysgnath bite form, in particular mandibular prognathism. After professional oral hygiene treatment and restorative dental procedures the final prosthodontic treatment plan was an upper and lower telescopic overdenture. Facebow and an intraoral central bearing device were used to determine the centric relation position during the procedures. Summary: In developing societies, the role of dentists is increasingly valued in improving the quality of life of the elderly, whereas a well-functioning, aesthetic prosthodontic treatment has an impact on many aspects of our patients' lives. Overdentures seem to be an ideal choice as a prosthodontic treatment, they meet the requirements of gerostomatology.